Richness and abundance of birds in green areas of San Cristobal de Las Casas city, Chiapas, Mexico - Medrano-Guzmán, Ana Patricia (2020)
Green areas in urban districts are important elements for bird conservation. In this study, we estimated bird abundance within green areas in the urban district of San Cristobal de Las Casas, state of Chiapas, Mexico. We identified a total of 75 bird species in ten green areas of different sizes from February of 2016 through July of 2016. We related bird presence to environmental variables at two geographical scales (local and landscape). Nonparametric analyses were used to compare richness and abundance of birds between green areas and size categories. The percentage of vegetation area was the most important variable that positively correlated with species richness and abundance. However, negative correlations were found between species richness and abundance and the percentage coverage of canopy, buildings, pavement and sampled green areas. The spatial heterogeneity of vertical vegetation structure in green areas was important to increase the diversity of avifauna. The maintenance and increase of green areas in cities is important to protect and increase the diversity of birds in urban areas.